Resveratrol Activates Autophagy via the AKT/mTOR Signaling Pathway to Improve Cognitive Dysfunction in Rats With Chronic Cerebral Hypoperfusion - Wang, Nan; He, Jinting; Pan, Chengliang; Wang, Jiaoqi; Ma, Ming; Shi, Xinxiu; Xu, Zhongxin (Frontiers in Neuroscience, 2019)
Objectives: Effects of resveratrol on autophagy in frontal cortex and hippocampus of CCH model rats were observed, and neuroprotective effects of resveratrol on CCH rats and the mechanism of action of AKT/mTOR signaling pathway were researched. Method: The CCH model was made by permanently ligating the bilateral common carotid arteries. Neurological deficit scores and Morris water maze test were used to test the behavioral changes and the cognitive function of rats; HE and Tunel staining were used to detect pathological and neuronal apoptosis in frontal cortex and hippocampus. ELISA was used to detect oxidative stress factor and brain injury markers. Immunofluorescence and Western blot were used to detect the expression of apoptosis, autophagy and AKT/mTOR signaling pathway-related proteins in frontal cortex and hippocampus. Results: After resveratrol treatment, the neurological function scores of CCH rats were reduced, cognitive dysfunction caused by long-term hypoxia and hypoperfusion was improved, and the pathological damage in frontal cortex and hippocampus was reduced; The expression of oxidative stress and brain injury markers decreased the apoptotic rate of neurons in the frontal cortex and hippocampus. The resveratrol can activate autophagy and inhibit the expression of AKT/mTOR signaling pathway-related proteins. PI3K inhibitor reversed the protective effect of resveratrol. Conclusions: The resveratrol can improve the cognitive function damage of CCH model rats, and reduce the damage of oxidative stress on neurons in frontal cortex and hippocampus by activating autophagy and inhibit neuronal apoptosis. This effect may be regulated by the AKT/mTOR signaling pathway.